Operation management of academic libraries in Hong Kong under COVID-19 - Yu, Pui Yik; Lam, Ernest Tak Hei; Chiu, Dickson K.W. (Library hi tech, 2023)
PurposeThis research studies the influence of the COVID-19 pandemic on the operation management of Hong Kong academic libraries for understanding the difficulties and challenges for librarians to adapt to the special arrangements during the pandemic.Design/methodology/approachQualitative semi-structured interviews were conducted with librarians in major universities and higher education institutions of Hong Kong. Participants were interviewed either in the face-to-face format or text-based format.FindingsParticipants provided a broad scope about the actual library management and operation changes during the COVID-19. According to the respondents, the most challenging problem for librarians during COVID-19 was to strike a balance between concerns of library staff and users. While they described how these arrangements and changes affected the service quality of academic libraries from different perspectives, the pandemic situation also brought some opportunities, such as pushing the digitalization of all collections and using online resources for future development. A hybrid model for library service would be more common in the future with more demands toward online resources and digital collection, in which academic libraries should be prepared after the pandemic.Originality/valueThis paper provided broad insights into library management and the future development of academic libraries for the post-COVID-19 period. There are scant studies of this topic, especially in an Asian metropolis context with dense population, small campus and limited library physical spaces.